(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Abstract— Real time information such as safety issues, budget, mode of transportation, altitude of the destination place, likelihood of sports activities etc. has direct impact on the Group recommendation in case of Tourism domain. Tourist spot recommendation based upon a group overall preference requires several analyses in order to avoid both the least misery and most pleasure approach. In a heterogeneous group which may comprises of children’s, older age people, spouse, colleagues may lead to different preferences by each individual. This paper deals with hill station recommendation considering the practical issues and requirement of tourist group in order to maximize the satisfaction level of overall group.